Lack of Health Insurance Among Adults Aged 18 to 64 Years: Findings From the 2013 Behavioral Risk Factor Surveillance System - Okoro, Catherine A. (Prev Chronic Dis, 2015)
INTRODUCTION: The objective of this study was to estimate the prevalence of lack of health insurance among adults aged 18 to 64 years for each state and the United States and to describe populations without insurance. METHODS: We used 2013 Behavioral Risk Factor Surveillance System data to categorize states into 3 groups on the basis of the prevalence of lack of health insurance in each state compared with the national average (21.5%; 95% confidence interval, 21.1%–21.8%): high-insured states (states with an estimated prevalence of lack of health insurance below the national average), average-insured states (states with an estimated prevalence of lack of health insurance equivalent to the national average), and low-insured states (states with an estimated prevalence of lack of health insurance higher than the national average). We used bivariate analyses to compare the sociodemographic characteristics of these 3 groups after age adjustment to the 2000 US standard population. We examined the distribution of Medicaid expansion among the 3 groups. RESULTS: Compared with the national age-adjusted prevalence of lack of health insurance, 24 states had lower rates of uninsured residents, 12 states had equivalent rates of uninsured, and 15 states had higher rates of uninsured. Compared with adults in the high-insured and average-insured state groups, adults in the low-insured state group were more likely to be non-Hispanic black or Hispanic, to have less than a high school education, to be previously married (divorced, widowed, or separated), and to have an annual household income at or below $35,000. Seventy-one percent of high-insured states were expanding Medicaid eligibility compared with 67% of average-insured states and 40% of low-insured states. CONCLUSION: Large variations exist among states in the estimated prevalence of health insurance. Many uninsured Americans reside in states that have opted out of Medicaid expansion.